Unexpected medical undergraduate simulation training (UMUST): can unexpected medical simulation scenarios help prepare medical students for the transition to foundation year doctor?. Issue 1 (December 2016) - Watmough, Simon; Box, Helen; Bennett, Nick; Stewart, Alison; Farrell, Michael
Abstract Background Preparing medical students with the skills necessary to deal with emergency situations as junior doctors can be challenging due to the complexities of creating authentic 'real life' experiences in artificial environments. The following paper is an evaluation of the UMUST (Unexpected Medical Undergraduate Simulation Training) project; a high-fidelity simulation based training programme designed to emulate the experience of dealing with medical emergencies for final year medical students preparing for practice as Foundation Year trainees. Methods Final year medical students from Liverpool University who undertake their clinical placements at Blackpool Teaching Hospitals NHS Foundation Trust and St. Helens & Knowsley Teaching Hospitals NHS Trust were randomly allocated into groups and took part in a series of four unexpected simulation based scenarios. At the beginning of the week in which the scenarios ran, participants were issued with a hospital bleep which they carried with them during their placement. At an unknown time to them, the participants were bleeped to attend a simulated emergency scenario, and on arrival to the Clinical Skills and Simulation facility, members of the education team undertook a standardised simulation scenario. Each session was recorded on video which the participants subsequently watched as part of a debriefing process. An assessment tool was developed to gauge whether the participants made progress in their learning over the course of the four sessions. Focus groups were held with the participants in order to evaluate their experience of the programme, and questionnaires were later distributed to all participants once they had begun working as a Foundation Year trainee. The questionnaires asked them how relevant UMUST was in preparing them for dealing with medical emergencies. Results The questionnaires and the focus groups clearly showed that the doctors felt like UMUST was very valuable in preparing them to work as junior doctors. They had enjoyed taking part in UMUST and thought was a realistic and useful part of their undergraduate training. Conclusions The feedback from the focus groups and the subsequent questionnaires clearly demonstrate that participants felt the UMUST programme helped to prepare them as junior doctors in terms of dealing with emergency situations.